PENGARUH LATIHAN TENDANGAN DENGAN MENGUNAKAN BEBAN TERHADAP KECEPATAN TENDANGAN MAWASHINGERI PADA ATLET KARATE LEMKARI KECAMATAN TAMBANG - Adi Tyawarman Z; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is still the speed of the kick when attackingbefore you shoot at the opponent, so the power of the kick in the goal is not good. Usethe attack of this athlete in vain without getting points. The aim of this research is tostudy kick training simulation using Mawashi-Geri kick speed on Lemkari karateathletics in my mining district. This investigation is being conducted in Lemkari dojo,district judge of Jalan Regent, Kampar Regency. The study was conducted fromDecember to April 2020. The population sampled in this study were all karate clubsoccupied by 10 people. Based on the results of the analysis of pre- and post-test data,there is a difference in the amount that increases. After completing the test, this studyprovides a method to increase the speed of Mawashi Geri's pedaling steps for 16meetings using the method of practicing Mawashi Geri's pedaling steps with weights.Finally, the researchers took a post-test of the Mawashi Geri exercise, which receivedthe work 16 times with the karate kick speed test, and obtained data from Lhitung0.1721and Ltabel0.258 with a normal distribution.Key Words: Effect of Kick Training, Kick speed